Compost Addition Enhanced Hyphal Growth and Sporulation of Arbuscular Mycorrhizal Fungi without Affecting Their Community Composition in the Soil - Yang, Wei; Gu, Siyu; Xin, Ying; Bello, Ayodeji; Sun, Wenpeng; Xu, Xiuhong (Frontiers in Microbiology, 2018)
Arbuscular mycorrhizal (AM) fungi form symbiotic associations with most crop plant species in agricultural ecosystems, and are conspicuously influenced by various agricultural practices. To understand the impact of compost addition on AM fungi, we examined effect of four compost rates (0, 11.25, 22.5, and 45 Mg/ha) on the abundance and community composition of AM fungi in seedling, flowering, and mature stage of soybean in a 1-year compost addition experiment system in Northeast China. Soybean [Glycine max (L.) Merrill] was used as test plant. Moderate (22.5 Mg/ha) and high (45 Mg/ha) levels of compost addition significantly increased AM root colonization and extraradical hyphal (ERH) density compared with control, whereas low (11.5 Mg/ha) level of compost addition did not cause significant increase in AM root colonization and ERH density. AM fungal spore density was significantly enhanced by all the compost rates compared with control. The temporal variations analysis revealed that, AM root colonization in seedling stage was significantly lower than in flowering and mature stage. Although AM fungal operational taxonomic unit richness and community composition was unaffected by compost addition, some abundant AM fungal species showed significantly different response to compost addition. In mature stage, Rhizophagus fasciculatum showed increasing trend along with compost addition gradient, whereas the opposite was observed with Paraglomus sp. In addition, AM fungal community composition exhibited significant temporal variation during growing season. Further analysis indicated that the temporal variation in AM fungal community only occurred in control treatment, but not in low, moderate, and high level of compost addition treatments. Our findings highlighted the significant effects of compost addition on AM growth and sporulation, and emphasized that growth stage is a stronger determinant than 1-year compost addition in shaping AM fungal community in black soil of Northeast China.